Świat fashion, czyli o anglicyzmach modowych w polskiej współczesnej prasie kobiecej - Kaczmarek, Anna (Słowo. Studia językoznawcze, 2014)
The article describes the English borrowings related to the topic of fashion, occurring in contemporary Polish women’s magazines. Featured anglicisms are the names of both the people involved with the world of fashion, as well as various pieces of clothing, accessories and clothing styles. In addition, the analysis of this kind vocabulary and women’s magazines inspires for further linguistic research, such as those related to the professional language of fashion journalists, authors attempts to cope with fashionable English language or characteristics persuasive measures used in such texts.